Report on proposed new interior design scheme for Creative Zen Retail Shop, at Lot No. 5, Jalan PJU 5, Kota Damansara, 46780, Petaling Jaya, Selangor Darul Ehsan / Mohammad Shafie Ahmad Tohar - Ahmad Tohar, Mohammad Shafie (Faculty of Architecture, Planning and Surveying, 2010)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed new interior design scheme of Creative Zen Retail Shop for Multi-Tronic Sdn. Bhd. at Lot no. 5, Jalan PJU 5, 46780, Petaling Jaya. The concept and image is also apply to both interior and exterior to appeal the centre will be able to lure more customers who were always keen in our design values of the product. There were several researches done to succeed this retail shop final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Multi-Tronic demands in terms of function and aesthetic value.